6(3n-1)=(7n+4)+7

Simple and best practice solution for 6(3n-1)=(7n+4)+7 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6(3n-1)=(7n+4)+7 equation:


Simplifying
6(3n + -1) = (7n + 4) + 7

Reorder the terms:
6(-1 + 3n) = (7n + 4) + 7
(-1 * 6 + 3n * 6) = (7n + 4) + 7
(-6 + 18n) = (7n + 4) + 7

Reorder the terms:
-6 + 18n = (4 + 7n) + 7

Remove parenthesis around (4 + 7n)
-6 + 18n = 4 + 7n + 7

Reorder the terms:
-6 + 18n = 4 + 7 + 7n

Combine like terms: 4 + 7 = 11
-6 + 18n = 11 + 7n

Solving
-6 + 18n = 11 + 7n

Solving for variable 'n'.

Move all terms containing n to the left, all other terms to the right.

Add '-7n' to each side of the equation.
-6 + 18n + -7n = 11 + 7n + -7n

Combine like terms: 18n + -7n = 11n
-6 + 11n = 11 + 7n + -7n

Combine like terms: 7n + -7n = 0
-6 + 11n = 11 + 0
-6 + 11n = 11

Add '6' to each side of the equation.
-6 + 6 + 11n = 11 + 6

Combine like terms: -6 + 6 = 0
0 + 11n = 11 + 6
11n = 11 + 6

Combine like terms: 11 + 6 = 17
11n = 17

Divide each side by '11'.
n = 1.545454545

Simplifying
n = 1.545454545

See similar equations:

| 0.6(x-5)=-10+4 | | (16+2x)(28+2x)=748 | | 4x-4-2x=4 | | p-46=-11 | | 0.92+x(0.2)=y | | 8=2w+7/6+7w+6/2 | | (-5u+7w-z)/(u+w-z) | | b/7-13=12 | | Y-5x=13 | | x^2+10x=200 | | 4(4x+3)+6=16x+18 | | 120(n-3)=600 | | 4(y+3)+y=2(y+4)-4 | | 5.4x+3.4=14.2 | | 2x^2+5x^4-12x^3=0 | | 2x-3/9+x+1/2=x-4 | | -24+6x=8(3x+6) | | -b+1.8=5.3 | | 4x-5/3-7x=2/1 | | -5(t-3)+7t=4t-2 | | 10p+9+11=-2(2p+4)-3(2p-2) | | (x+3)2-4=0 | | 6n+12=78 | | -7=-7.5z-(-7z+3) | | log[4](2x-9)-log[4](x-8)=3 | | 3(x+9)=6x | | 2=x-4(2x+3) | | 8(r+2)=54 | | 7x=12x-45 | | (+15)+(-7)+(+1)= | | y=57-2 | | 2x+4x=3x+3 |

Equations solver categories